Parallels and Overlap: The Integration of Homeostatic Signals by Mesolimbic Dopamine Neurons - Hsu, Ted M.; McCutcheon, James E.; Roitman, Mitchell F. (Frontiers in Psychiatry, 2018)
Motivated behaviors are often initiated in response to perturbations of homeostasis. Indeed, animals and humans have fundamental drives to procure (appetitive behaviors) and eventually ingest (consummatory behaviors) substances based on deficits in body fluid (e.g. thirst) and energy balance (e.g. hunger). Consumption, in turn, reinforces motivated behavior and is therefore considered rewarding. Uncovering the physiological mechanisms that underlie reinforcement and reward seeking has been particularly important in understanding health issues like obesity where individuals consume palatable, unhealthy foods beyond metabolic need. Over the years, the constructs of homeostatic (within the purview of the hypothalamus) and non-homeostatic (within the purview of mesolimbic circuitry) have been used to describe need-based versus need-free consumption. However, a growing body of literature now demonstrates that mesolimbic circuits and “higher-order” brain regions are also profoundly influenced by changes to physiological state, which in turn generate behaviors that are poised to maintain homeostasis. Mesolimbic pathways, particularly dopamine neurons of the ventral tegmental area (VTA) and their projections to nucleus accumbens (NAc), can be robustly modulated by a variety of energy balance signals, including post-ingestive feedback relaying nutrient content and hormonal signals reflecting hunger and satiety. Moreover, physiological states can also impact VTA-NAc responses to non-nutritive rewards, such as drugs of abuse. Coupled with recent evidence showing hypothalamic structures are modulated in anticipation of replenished need, the lines between circuits that convey perturbations in homeostasis and those that drive motivated behavior have been blurred. In the current review, we examine data that have revealed the importance of mesolimbic dopamine neurons and their downstream pathways as a dynamic neurobiological mechanism that provides an interface between physiological state, perturbations to homeostasis, and reward-seeking behaviors.